Understanding of Sex Education in Early Children in View from The Role of Parenting Parents - Aisyah, A; Insani, Aulia (Early Childhood Research Journal (ECRJ), 2023)
This research was conducted to find out how the role of parenting influences the introduction of sexual education in children aged 4-5 years. The research method used is descriptive qualitative by collecting data through observation, interviews and documentation. Then, the subjects of this study were 3 children who had democratic, authoritarian and permissive parenting styles. Informants taken were 3 people who were parents, siblings and grandmothers who helped care for the object.Based on the research that has been done, the results show that the type of parenting applied by parents causes differences in behavior towards knowledge of sexual education in children aged 4-5 years.